Lattice copper and carbon vacancy co-modified zero-valent iron, preparation method thereof and application of lattice copper and carbon vacancy co-modified zero-valent iron in catalysis of dechlorination of carbon tetrachloride in water
By preparing lattice copper and carbon vacancies to co-modify zero-valent iron, the problem of slow and incomplete dechlorination of carbon tetrachloride in the prior art is solved, and the rapid complete dechlorination of carbon tetrachloride and high recovery of chlorine-free products is achieved, which is suitable for deep dechlorination of carbon tetrachloride in groundwater.
Patent Information
- Application Number
- CN202411838504.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The prior art has slow and incomplete dechlorination problems when dechlorinating carbon tetrachloride in catalytic water bodies, and may produce secondary pollutants, making it difficult to achieve complete removal of carbon tetrachloride.
By preparing lattice copper and carbon vacancies, the zero-valent iron is modified by co-modifying zero-valent iron, and the consumption of the surface iron oxide layer during high-temperature ball milling, oxygen volatility and carbon reduction reactions are used to induce the formation of carbon vacancies, promote the lattice doping of copper in the zero-valent iron core, and form a catalyst with a symbiotic structure.
The rapid and complete dechlorination of carbon tetrachloride is achieved, the product is a chlorine-free product, the product recovery rate is greater than 80%, and it works effectively in a wide pH environment, with excellent reusability and long-term stability.
Smart Images

Figure CN119680544A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to lattice copper and carbon vacancy co-modified zero-valent iron and a preparation method thereof and application thereof in catalyzing dechlorination of carbon tetrachloride in water, belonging to the technical field of functional catalysts and groundwater pollution remediation thereof. Background Art
[0002] Carbon tetrachloride is ubiquitous in groundwater, posing a considerable potential threat to ecological safety and human health. However, due to the low electron affinity of carbon tetrachloride, the energy barrier required for its dechlorination is high. And as the dechlorination reaction proceeds, the structural saturation caused by hydrogenation or the reduction in the number of chlorine substituents usually leads to a significant decrease in the electron affinity of the intermediates, which complicates the completion of the dechlorination reaction. In addition, the dechlorination intermediates may be more toxic, thereby increasing the risk of water re-contamination. Therefore, sustainable and efficient chemical dechlorination solutions are urgently needed to mitigate secondary pollution of water bodies after dechlorination treatment.
[0003] Zero-valent iron reduction dechlorination provides an economical, safe and efficient way to control pollution and ensure ecological security. However, due to the inherent electron competition between organic matter and water, slow and incomplete dechlorination remains extremely challenging, mainly due to the hydrophilicity of zero-valent iron, which makes its selectivity for target pollutants lower than that for water, and the dense structural characteristics of the surface iron oxide layer hinder electron transport and interfacial mass transfer, and zero-valent iron dechlorination is completely determined by the direct electron transfer mechanism, while the dechlorination of low-chlorine organic matter is more likely to be dominated by indirect reduction of active hydrogen. Therefore, the synergistic enhancement of the dual mechanisms of direct electron transfer and indirect reduction of active hydrogen is crucial to achieve complete dechlorination of carbon tetrachloride by zero-valent iron. In order to achieve complete dechlorination of carbon tetrachloride, it is necessary to rationally utilize the iron oxide layer. The Chinese patent with application number CN116553702A discloses a method for reduction dechlorination of a composite surfactant coupled to a sulfide micron zero-valent iron system, that is, using a composite surfactant HTAB and Tween80 coupled to a sulfide micron zero-valent iron material as a reducing agent to reduce carbon tetrachloride in water. However, due to its limited reduction ability and single direct electron transfer reduction dechlorination mechanism, carbon tetrachloride is difficult to be completely removed in the groundwater environment. In order to achieve rapid and complete dechlorination of carbon tetrachloride without producing secondary pollutants, it is still necessary to further develop modified zero-valent iron materials with high hydrophobicity, high electron transfer ability and effective utilization of active hydrogen. Summary of the invention
[0004] The invention aims at the technical problem of slow and incomplete dechlorination caused by inherent electron competition between carbon tetrachloride and water, and provides a lattice copper and carbon vacancy co-modified zero-valent iron and a preparation method thereof and an application of the zero-valent iron in catalyzing dechlorination of carbon tetrachloride in water.
[0005] The technical solution of the present invention:
[0006] One of the purposes of the present invention is to provide a method for preparing lattice copper and carbon vacancy co-modified zero-valent iron, the method comprising the following steps:
[0007] (1) performing a first ball milling treatment on citric acid under an argon atmosphere to obtain a precursor A;
[0008] (2) adding micronized zero-valent iron to precursor A and continuing to perform a second ball milling treatment under an argon atmosphere to obtain precursor B;
[0009] (3) Copper powder is added to the precursor B and the precursor B is subjected to a third ball milling treatment under an argon atmosphere to obtain zero-valent iron co-modified with lattice copper and carbon vacancies.
[0010] It is further defined that the mass ratio of citric acid, micronized zero-valent iron and copper powder is 0.0958-0.6182:2.7830-4.4891:0.5109-2.2170.
[0011] It is further defined that the particle size of the micron zero-valent iron is 30-50 μm.
[0012] It is further defined that the ball-to-material ratio of the first ball milling, the second ball milling and the third ball milling is 10:1, wherein the ratio of zirconia balls with a diameter of 6 mm and that with a diameter of 10 mm is 6:1.
[0013] It is further defined that the first ball milling treatment in (1) is performed at a rotation speed of 550 r / min and for a time of 4 h.
[0014] It is further defined that the second ball milling treatment in (2) has a rotation speed of 550 r / min and a time of 2 h.
[0015] It is further defined that the third ball milling treatment in (3) has a rotation speed of 550 r / min and a time of 6 h.
[0016] The second object of the present invention is to provide a lattice copper and carbon vacancy co-modified zero-valent iron prepared by the above method.
[0017] The third object of the present invention is to provide an application of the above-mentioned lattice copper and carbon vacancy co-modified zero-valent iron, specifically for catalyzing the chemical dechlorination of carbon tetrachloride in water.
[0018] A fourth object of the present invention is to provide a method for dechlorinating carbon tetrachloride in groundwater by using the above-mentioned lattice copper and carbon vacancy co-modified zero-valent iron to catalyze. Specifically, using lattice copper and carbon vacancy co-modified zero-valent iron as catalysts, at 20-25°C and an oscillation rate of 200r / min, catalytic degradation of groundwater containing carbon tetrachloride is carried out for 1-20h, thereby achieving complete dechlorination of carbon tetrachloride in groundwater.
[0019] It is further defined that the initial concentration of carbon tetrachloride in groundwater is 5 mg / L.
[0020] Beneficial effects:
[0021] The present invention is based on the in-situ sacrificial strategy of the iron oxide layer, and ingeniously utilizes the consumption of the surface iron oxide layer, oxygen volatilization and carbon reduction during high-temperature ball milling to induce the formation of carbon vacancies, promote the lattice doping of copper in the zero-valent iron core (similar to the Kirkendall effect), promote the outward release of iron and the inward migration of copper (lattice doping), and prepare lattice copper and carbon vacancy co-modified zero-valent iron with a symbiotic structure. Compared with the prior art, it has at least the following advantages:
[0022] (1) The lattice copper and carbon vacancy co-modified zero-valent iron provided by the present invention can achieve rapid and complete dechlorination of carbon tetrachloride, and the products are chlorine-free products (methane, carbon monoxide, formic acid), and the product recovery rate is greater than 80%. The dechlorination reaction can occur in a wide pH environment. In addition, the lattice copper and carbon vacancy co-modified zero-valent iron catalyst material has excellent reusability, providing superior reactivity and long-term stability for deep dechlorination of carbon tetrachloride in sustainable groundwater treatment.
[0023] (2) The present invention utilizes copper doping in the lattice of the zero-valent iron core to destroy the continuity of the zero-valent iron bcc lattice, induce the release of core electrons, and promote the reduction transformation from carbon tetrachloride to chloroform and then to dichloromethane. The formed carbon vacancies serve as the generation site and bridge of active hydrogen, allowing the active hydrogen to spontaneously migrate to the adjacent zero-valent iron and participate in the subsequent dechlorination process from dichloromethane to monochloromethane and then to chlorine-free products. This symbiotic structure regulates the coupling mechanism of direct electron transfer and indirect reduction of active hydrogen, reduces the reaction energy barrier, and achieves thermodynamically favorable continuous and complete dechlorination. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 A comparison diagram of the effects of lattice copper and carbon vacancy co-modified zero-valent iron in degrading carbon tetrachloride at different copper-iron molar ratios prepared in Examples 1 to 4;
[0025] Figure 2 A comparison diagram of the effects of lattice copper and carbon vacancy co-modified zero-valent iron in degrading carbon tetrachloride at different carbon-iron molar ratios prepared in Examples 5 to 8;
[0026] Figure 3 This is a comparison chart of the degradation rates of carbon tetrachloride at different pH values by lattice copper and carbon vacancy co-modified zero-valent iron prepared in Example 9;
[0027] Figure 4 TEM photo and partial magnified image of lattice copper and carbon vacancy co-modified zero-valent iron prepared in Example 10;
[0028] Figure 5This is a diagram showing the product changes during the degradation of carbon tetrachloride by zero-valent iron modified with lattice copper and carbon vacancies prepared in Example 10. DETAILED DESCRIPTION
[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0030] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0031] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0032] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art, and the purity of the solid and liquid reagents used is analytically pure.
[0033] Example 1
[0034] (1) 0.1545 g of citric acid was weighed and added into a 100 mL stainless steel tank of a planetary ball mill, and zirconium oxide balls (6 mm diameter and 10 mm diameter zirconium oxide balls were in a ratio of 6:1, and the material ratio was 10:1) were added and ball milled at a speed of 550 r / min for 4 h under an argon atmosphere to obtain a precursor A;
[0035] (2) 3.1868 g of micronized zero-valent iron was weighed and added to the above-mentioned precursor A, and zirconium oxide balls (6 mm diameter and 10 mm diameter zirconium oxide balls were in a ratio of 6:1, and the material ratio was 10:1) were added to a 100 mL stainless steel tank of a planetary ball mill and ball milled at a speed of 550 r / min for 2 h under an argon atmosphere to obtain precursor B;
[0036] (3) Weigh 0.3642 g of copper powder so that the copper-iron molar ratio is 0.1, add the above-mentioned precursor B, continue to add zirconium oxide balls (the ratio of 6 mm diameter and 10 mm diameter zirconium oxide balls is 6:1, and the material ratio is 10:1) in a 100 mL stainless steel tank of a planetary ball mill, and ball mill at a speed of 550 r / min for 6 h under an argon atmosphere to prepare lattice copper and carbon vacancy co-modified zero-valent iron with a symbiotic structure, named 0.1.
[0037] Example 2
[0038] (1) 0.1545 g of citric acid was weighed and added into a 100 mL stainless steel tank of a planetary ball mill, and zirconium oxide balls (6 mm diameter and 10 mm diameter zirconium oxide balls were in a ratio of 6:1, and the material ratio was 10:1) were added and ball milled at a speed of 550 r / min for 4 h under an argon atmosphere to obtain a precursor A;
[0039] (2) 3.1868 g of micronized zero-valent iron was weighed and added to the above-mentioned precursor A, and zirconium oxide balls (6 mm diameter and 10 mm diameter zirconium oxide balls were in a ratio of 6:1, and the material ratio was 10:1) were added to a 100 mL stainless steel tank of a planetary ball mill and ball milled at a speed of 550 r / min for 2 h under an argon atmosphere to obtain precursor B;
[0040] (3) 1.0926 g of copper powder was weighed to make a copper-iron molar ratio of 0.3, and the above-mentioned precursor B was added. Zirconia balls (6 mm diameter and 10 mm diameter zirconia balls were added in a ratio of 6:1, and the material ratio was 10:1) were added to a 100 mL stainless steel tank of a planetary ball mill and ball milled at a speed of 550 r / min for 6 h under an argon atmosphere to prepare a symbiotic structure of lattice copper and carbon vacancy co-modified zero-valent iron, named 0.3.
[0041] Example 3
[0042] (1) 0.1545 g of citric acid was weighed and added into a 100 mL stainless steel tank of a planetary ball mill, and zirconium oxide balls (6 mm diameter and 10 mm diameter zirconium oxide balls were in a ratio of 6:1, and the material ratio was 10:1) were added and ball milled at a speed of 550 r / min for 4 h under an argon atmosphere to obtain a precursor A;
[0043] (2) 3.1868 g of micronized zero-valent iron was weighed and added to the above-mentioned precursor A, and zirconium oxide balls (6 mm diameter and 10 mm diameter zirconium oxide balls were in a ratio of 6:1, and the material ratio was 10:1) were added to a 100 mL stainless steel tank of a planetary ball mill and ball milled at a speed of 550 r / min for 2 h under an argon atmosphere to obtain precursor B;
[0044] (3) Weigh 1.8210 g of copper powder so that the copper-iron molar ratio is 0.5, add the above-mentioned precursor B, continue to add zirconium oxide balls (the ratio of 6 mm diameter and 10 mm diameter zirconium oxide balls is 6:1, and the material ratio is 10:1) in a 100 mL stainless steel tank of a planetary ball mill, and ball mill at a speed of 550 r / min for 6 h under an argon atmosphere to prepare lattice copper and carbon vacancy co-modified zero-valent iron with a symbiotic structure, named 0.5.
[0045] Example 4
[0046] (1) 0.1545 g of citric acid was weighed and added into a 100 mL stainless steel tank of a planetary ball mill, and zirconium oxide balls (6 mm diameter and 10 mm diameter zirconium oxide balls were in a ratio of 6:1, and the material ratio was 10:1) were added and ball milled at a speed of 550 r / min for 4 h under an argon atmosphere to obtain a precursor A;
[0047] (2) 3.1868 g of micronized zero-valent iron was weighed and added to the above-mentioned precursor A, and zirconium oxide balls (6 mm diameter and 10 mm diameter zirconium oxide balls were in a ratio of 6:1, and the material ratio was 10:1) were added to a 100 mL stainless steel tank of a planetary ball mill and ball milled at a speed of 550 r / min for 2 h under an argon atmosphere to obtain precursor B;
[0048] (3) Weigh 2.5494 g of copper powder so that the copper-iron molar ratio is 0.7, add the above-mentioned precursor B, continue to add zirconium oxide balls (the ratio of 6 mm diameter and 10 mm diameter zirconium oxide balls is 6:1, and the material ratio is 10:1) in a 100 mL stainless steel tank of a planetary ball mill, and ball mill at a speed of 550 r / min for 6 h under an argon atmosphere to prepare lattice copper and carbon vacancy co-modified zero-valent iron with a symbiotic structure, named 0.7.
[0049] The lattice copper and carbon vacancy co-modified zero-valent iron prepared in Examples 1 to 4 above were used to degrade carbon tetrachloride with an initial concentration of 5 mg / L. The amount of lattice copper and carbon vacancy co-modified zero-valent iron added was 0.2 g / L. The efficiency of degrading carbon tetrachloride is shown in FIG. Figure 1 As shown by Figure 1 It can be seen that zero-valent iron co-modified with lattice copper and carbon vacancies can completely degrade carbon tetrachloride within 5 hours, and it can be determined that the modified material with a copper-iron molar ratio of 0.5 has the fastest carbon tetrachloride degradation rate and the best performance.
[0050] Example 5
[0051] (1) 0.1539 g of citric acid was weighed and added into a 100 mL stainless steel tank of a planetary ball mill, and zirconium oxide balls (the ratio of 6 mm diameter to 10 mm diameter zirconium oxide balls was 6:1, and the material ratio was 10:1) were added and ball milled at a speed of 550 r / min for 4 h under an argon atmosphere to obtain a precursor A;
[0052] (2) 4.4891 g of micronized zero-valent iron was weighed to make the carbon-iron molar ratio 0.06, and the above-mentioned precursor A was added, and zirconium oxide balls (6 mm diameter and 10 mm diameter zirconium oxide balls were in a ratio of 6:1, and the material ratio was 10:1) were added to a 100 mL stainless steel tank of a planetary ball mill, and ball milling was carried out at a speed of 550 r / min for 2 h under an argon atmosphere to obtain precursor B;
[0053] (3) Weigh 1.8132 g of copper powder, add the above-mentioned precursor B, continue to add zirconium oxide balls (the ratio of 6 mm diameter and 10 mm diameter zirconium oxide balls is 6:1, and the material ratio is 10:1) in a 100 mL stainless steel tank of a planetary ball mill, and ball mill at a speed of 550 r / min for 6 h under an argon atmosphere to prepare lattice copper and carbon vacancy co-modified zero-valent iron with a symbiotic structure, named 0.06.
[0054] Example 6
[0055] (1) 0.3078 g of citric acid was weighed and added into a 100 mL stainless steel tank of a planetary ball mill, and zirconium oxide balls (the ratio of 6 mm diameter to 10 mm diameter zirconium oxide balls was 6:1, and the material ratio was 10:1) were added and ball milled at a speed of 550 r / min for 4 h under an argon atmosphere to obtain a precursor A;
[0056] (2) 4.4891 g of micronized zero-valent iron was weighed to make the carbon-iron molar ratio of 0.12, and the above-mentioned precursor A was added, and zirconium oxide balls (6 mm diameter and 10 mm diameter zirconium oxide balls were in a ratio of 6:1, and the material ratio was 10:1) were added to a 100 mL stainless steel tank of a planetary ball mill, and ball milling was carried out at a speed of 550 r / min for 2 h under an argon atmosphere to obtain precursor B;
[0057] (3) Weigh 1.8132 g of copper powder, add the above-mentioned precursor B, continue to add zirconium oxide balls (the ratio of 6 mm diameter and 10 mm diameter zirconium oxide balls is 6:1, and the material ratio is 10:1) in a 100 mL stainless steel tank of a planetary ball mill, and ball mill at a speed of 550 r / min for 6 h under an argon atmosphere to prepare lattice copper and carbon vacancy co-modified zero-valent iron with a symbiotic structure, named 0.12.
[0058] Example 7
[0059] (1) 0.4617 g of citric acid was weighed and added into a 100 mL stainless steel tank of a planetary ball mill, and zirconium oxide balls (the ratio of 6 mm diameter to 10 mm diameter zirconium oxide balls was 6:1, and the material ratio was 10:1) were added and ball milled at a speed of 550 r / min for 4 h under an argon atmosphere to obtain a precursor A;
[0060] (2) 4.4891 g of micronized zero-valent iron was weighed to make the carbon-iron molar ratio of 0.18, and the above-mentioned precursor A was added, and zirconium oxide balls (6 mm diameter and 10 mm diameter zirconium oxide balls were in a ratio of 6:1, and the material ratio was 10:1) were added to a 100 mL stainless steel tank of a planetary ball mill, and ball milling was carried out at a speed of 550 r / min for 2 h under an argon atmosphere to obtain precursor B;
[0061] (3) Weigh 1.8132 g of copper powder, add the above-mentioned precursor B, continue to add zirconium oxide balls (the ratio of 6 mm diameter and 10 mm diameter zirconium oxide balls is 6:1, and the material ratio is 10:1) in a 100 mL stainless steel tank of a planetary ball mill, and ball mill at a speed of 550 r / min for 6 h under an argon atmosphere to prepare lattice copper and carbon vacancy co-modified zero-valent iron with a symbiotic structure, named 0.18.
[0062] Example 8
[0063] (1) 0.6156 g of citric acid was weighed and added into a 100 mL stainless steel tank of a planetary ball mill, and zirconium oxide balls (the ratio of 6 mm diameter to 10 mm diameter zirconium oxide balls was 6:1, and the material ratio was 10:1) were added and ball milled at a speed of 550 r / min for 4 h under an argon atmosphere to obtain a precursor A;
[0064] (2) 4.4891 g of micronized zero-valent iron was weighed to make the carbon-iron molar ratio 0.24, and the above-mentioned precursor A was added, and zirconium oxide balls (6 mm diameter and 10 mm diameter zirconium oxide balls were in a ratio of 6:1, and the material ratio was 10:1) were added to a 100 mL stainless steel tank of a planetary ball mill, and ball milling was carried out at a speed of 550 r / min for 2 h under an argon atmosphere to obtain precursor B;
[0065] (3) Weigh 1.8132 g of copper powder, add the above-mentioned precursor B, continue to add zirconium oxide balls (the ratio of 6 mm diameter and 10 mm diameter zirconium oxide balls is 6:1, and the material ratio is 10:1) in a 100 mL stainless steel tank of a planetary ball mill, and ball mill at a speed of 550 r / min for 6 h under an argon atmosphere to prepare lattice copper and carbon vacancy co-modified zero-valent iron with a symbiotic structure, named 0.24.
[0066] The lattice copper and carbon vacancy co-modified zero-valent iron prepared in Examples 5 to 8 above were used to degrade carbon tetrachloride with an initial concentration of 5 mg / L. The amount of lattice copper and carbon vacancy co-modified zero-valent iron added was 0.3 g / L. The efficiency of degrading carbon tetrachloride is shown in FIG. Figure 2 As shown by Figure 2 It can be determined that the modified material with a carbon-iron molar ratio of 0.12 has the fastest carbon tetrachloride degradation rate and the best performance.
[0067] Example 9
[0068] (1) 0.3291 g of citric acid was weighed and added into a 100 mL stainless steel tank of a planetary ball mill, and zirconium oxide balls (the ratio of 6 mm diameter to 10 mm diameter zirconium oxide balls was 6:1, and the material ratio was 10:1) were added and ball milled at a speed of 550 r / min for 4 h under an argon atmosphere to obtain a precursor A;
[0069] (2) 3.7275 g of micronized zero-valent iron was weighed and added to the above-mentioned precursor A, and zirconium oxide balls (6 mm diameter and 10 mm diameter zirconium oxide balls were in a ratio of 6:1, and the material ratio was 10:1) were added to a 100 mL stainless steel tank of a planetary ball mill and ball milled at a speed of 550 r / min for 2 h under an argon atmosphere to obtain precursor B;
[0070] (3) Weigh 1.8132 g of copper powder, add the above-mentioned precursor B, continue to add zirconium oxide balls (the ratio of 6 mm diameter and 10 mm diameter zirconium oxide balls is 6:1, and the material ratio is 10:1) in a 100 mL stainless steel tank of a planetary ball mill, and ball mill at a speed of 550 r / min for 6 h under an argon atmosphere to prepare lattice copper and carbon vacancy co-modified zero-valent iron with a symbiotic structure.
[0071] The lattice copper and carbon vacancy co-modified zero-valent iron prepared in this embodiment were used to degrade carbon tetrachloride with an initial concentration of 5 mg / L. The amount of lattice copper and carbon vacancy co-modified zero-valent iron added was 0.3 g / L, and hydrochloric acid or sodium hydroxide was used to adjust the pH of the carbon tetrachloride solution to 3, 5, 7, 9, and 11, respectively. The efficiency of degrading carbon tetrachloride is shown in FIG. Figure 3 As shown by Figure 3 It can be determined that the dechlorination reaction can occur in a wide range of pH environments, especially at pH 3, where the degradation rate of carbon tetrachloride is the fastest and the performance is the best.
[0072] Example 10
[0073] (1) 0.6182 g of citric acid was weighed and added into a 100 mL stainless steel tank of a planetary ball mill, and zirconium oxide balls (the ratio of 6 mm diameter to 10 mm diameter zirconium oxide balls was 6:1, and the material ratio was 10:1) were added and ball milled at a speed of 550 r / min for 4 h under an argon atmosphere to obtain a precursor A;
[0074] (2) 3.1868 g of micronized zero-valent iron was weighed and added to the above-mentioned precursor A, and zirconium oxide balls (6 mm diameter and 10 mm diameter zirconium oxide balls were in a ratio of 6:1, and the material ratio was 10:1) were added to a 100 mL stainless steel tank of a planetary ball mill and ball milled at a speed of 550 r / min for 2 h under an argon atmosphere to obtain precursor B;
[0075] (3) Weigh 2.2170 g of copper powder, add the above-mentioned precursor B, continue to add zirconium oxide balls (the ratio of 6 mm diameter and 10 mm diameter zirconium oxide balls is 6:1, and the material ratio is 10:1) in a 100 mL stainless steel tank of a planetary ball mill, and ball mill at a speed of 550 r / min for 6 h in an argon atmosphere to prepare lattice copper and carbon vacancy co-modified zero-valent iron with a symbiotic structure.
[0076] The microstructure of the lattice copper and carbon vacancy co-modified zero-valent iron prepared in this example was characterized, and the results are as follows: Figure 4 As shown, a lattice “continuity break” corresponding to the Fe(110) facet was observed by aberration-corrected high-angle annular dark-field transmission electron microscopy, which may correspond to a Kirkendall-like effect of asymmetric displacement between iron and copper, and shows a large number of carbon vacancies and topological carbon defects.
[0077] The lattice copper and carbon vacancy co-modified zero-valent iron prepared in this embodiment are used to degrade carbon tetrachloride with an initial concentration of 5 mg / L. The amount of lattice copper and carbon vacancy co-modified zero-valent iron added is 0.3 g / L, and the product of carbon tetrachloride degradation is as follows: Figure 5 As shown by Figure 5 It can be determined that lattice copper and carbon vacancy co-modified zero-valent iron achieves rapid and complete dechlorination of carbon tetrachloride, and the products are chlorine-free products, namely 69% methane, 12% carbon monoxide, and 5% formic acid, with a recovery rate of more than 80%.
[0078] Although the present invention has been disclosed as above in the preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for preparing zero-valent iron co-modified by lattice copper and carbon vacancies, characterized in that: include: (1) performing a first ball milling treatment on citric acid under an argon atmosphere to obtain a precursor A; (2) adding micronized zero-valent iron to precursor A and continuing to perform a second ball milling treatment under an argon atmosphere to obtain precursor B; (3) Copper powder is added to the precursor B and the precursor B is subjected to a third ball milling treatment under an argon atmosphere to obtain zero-valent iron co-modified with lattice copper and carbon vacancies.
2. The preparation method according to claim 1, characterized in that: The mass ratio of citric acid, micron zero-valent iron and copper powder is 0.0958-0.6182:2.7830-4.4891:0.5109-2.2170.
3. The preparation method according to claim 1, characterized in that: The particle size of micron zero-valent iron is 30-50μm.
4. The preparation method according to claim 1, characterized in that: The ball-to-material ratio of the first ball milling, the second ball milling and the third ball milling is 10:1, among which the ratio of 6mm diameter zirconia balls to 10mm diameter is 6:
1.
5. The preparation method according to claim 1, characterized in that: The first ball milling process in (1) was performed at a rotation speed of 550 r / min and a time of 4 h.
6. The preparation method according to claim 1, characterized in that: The second ball milling process in (2) was carried out at a rotation speed of 550 r / min and a time of 2 h.
7. The preparation method according to claim 1, characterized in that: (3) The third ball milling process was carried out at a rotation speed of 550 r / min and a time of 6 h.
8. Lattice copper and carbon vacancy co-modified zero-valent iron prepared by the method according to any one of claims 1 to 7.
9. An application of the lattice copper and carbon vacancy co-modified zero-valent iron according to claim 8, characterized in that: Used to catalyze the chemical dechlorination of carbon tetrachloride in water.
10. A method for dechlorinating carbon tetrachloride in groundwater, characterized in that: Using the lattice copper and carbon vacancy co-modified zero-valent iron as described in claim 8 as a catalyst, catalytic degradation of groundwater containing carbon tetrachloride is carried out for 1-20 hours at 20-25°C and an oscillation rate of 200r / min, thereby achieving complete dechlorination of carbon tetrachloride in groundwater.
Citation Information
Patent Citations
Method for reductive dechlorination by coupling compound surfactant with sulfurized micron zero-valent iron system
CN116553702A
Chlorinated organic matter degrading and dechlorinating method
CN104961221A
Mesoporous carbon confinement nano zero-valent iron-palladium bimetallic powder and preparation method and application thereof
CN112264041A
Preparation method and application of citric acid doped sulfurized zero-valent iron composite material
CN115650400A
Grinding and / or dispersing aid of mineral materials in aqueous suspension, suspensions and uses thereof
CN1477997A